Determining how oxygen legacy affects trajectories of soil denitrifier community dynamics and N2O emissions - Louise B. Sennett; Constance A. Roco; Natalie Y. N. Lim; Joseph B. Yavitt; Peter Dörsch; Lars R. Bakken; James P. Shapleigh; Åsa Frostegård (Nature Communications, 2024)
Abstract Denitrification – a key process in the global nitrogen cycle and main source of the greenhouse gas N2O – is intricately controlled by O2. While the transition from aerobic respiration to denitrification is well-studied, our understanding of denitrifier communities’ responses to cyclic oxic/anoxic shifts, prevalent in natural and engineered systems, is limited. Here, agricultural soil is exposed to repeated cycles of long or short anoxic spells (LA; SA) or constant oxic conditions (Ox). Surprisingly, denitrification and N2O reduction rates are three times greater in Ox than in LA and SA during a final anoxic incubation, despite comparable bacterial biomass and denitrification gene abundances. Metatranscriptomics indicate that LA favors canonical denitrifiers carrying nosZ clade I. Ox instead favors nosZ clade II-carrying partial- or non-denitrifiers, suggesting efficient partnering of the reduction steps among organisms. SA has the slowest denitrification progression and highest accumulation of intermediates, indicating less functional coordination. The findings demonstrate how adaptations of denitrifier communities to varying O2 conditions are tightly linked to the duration of anoxic episodes, emphasizing the importance of knowing an environment’s O2 legacy for accurately predicting N2O emissions originating from denitrification.